ROLAND BARTHES’S THEORY OF SEMIOTICS ANALYSIS IN THE KOREAN DRAMA LOVELY RUNNER - Resfika, Diah Amanda; Sulistyo, Teguh; Cholifah, Maria (Ma Chung Press, 2025)
This study examines the application of Roland Barthes's semiotic theory in analyzing the Korean drama